Comet and Reverse Ajax : the next-generation Ajax 2.0 - Crane, Dave (FirstPress., 2008)
"Building applications that run inside a web browser has tremendous advantages over the traditional desktop podel - mainly because deployment is so much easier - but it is also subject to many constraints. There are no plug-ins, binary sockets, or special techniques here; Comete achieves all this on top of plain old HTTP. Engineering such a transformation is no mean feat, and this book will show you how to do so yourself. We'll point you to some of the frameworks and toolkits that make doing so possible and show you how to use them to develop production-ready Comet solutions."--Jacket